(E)-4-(3-Phenylisoxazol-5-yl)but-3-en-2-one - Sawengngen, Nattawut; Kolodina, Alexandra A.; Serdyuk, Olga (Molbank, 2019)
(E)-4-(3-Phenylisoxazol-5-yl)but-3-en-2-one was synthesized via the oxidative ring opening reaction of 2-(5-methylfuran-2-yl)-1-phenylethanone oxime, followed by the iodine mediated isomerization.
CRIS-Team WoS Importer:2019-11-12

Indolylvinyl Ketones: Building Blocks for the Synthesis of Natural Products and Bioactive Compounds - Trushkov, Igor V.; Uchuskin, Maxim G.; Abaev, Vladimir T.; Serdyuk, Olga (Synthesis-Stuttgart, 2019)
Indolylvinyl ketones are valuable building blocks that can be utilized for the synthesis of numerous natural products and bioactive molecules containing an indole core motif. Herein, we describe their application for the total synthesis of some alkaloids, their analogues, and a variety of other important compounds, with an emphasis on biologically active examples. 1Introduction 2 Functionalization of the Enone C=C Bond 2.1 Reduction 2.2 Michael Addition 2.3 Cycloaddition 3 Transformation of the Carbonyl Group 3.1 Reduction 3.2 Knoevenagel Reaction 3.3 Addition of Organometallic Compounds 3.4 Olefination 4 Reactions Involving the Enone Conjugate System C=C-C=? 4.1 Reactions with 1,2-Dinucleophiles 4.2 Reactions with Compounds Bearing an Active Methylene Group 4.3 Reactions with 1,3-Dinucleophiles 4.4 Reactions with 1,4-Dinucleophiles
CRIS-Team WoS Importer:2019-03-06

Non-heme iron catalysts for epoxidation and aziridination reactions of challenging terminal alkenes: towards sustainability - Tsogoeva, Svetlana; Fingerhut, Anja; Serdyuk, Olga (Green Chemistry, 2015)
Through catalytic epoxidation and aziridination of olefins versatile synthetic intermediates and subunits of biologically active compounds and pharmaceuticals -epoxides and aziridines-can be obtained. The focus of this review is on recent advances in the epoxidation and aziridination of challenging terminal alkenes with respect to safety of solvents or reagents used and atom economy aspects, as well as scope and limitations of developed non-heme iron catalysts. The still large research potential for sustainable and environmentally attractive iron-based catalysts in enantioselective epoxide and aziridine synthesis is demonstrated.

Synthesis of Isoxazolylvinyl Ketones from Substituted Furans - Serdyuk, Olga; Hampel, Frank; Abaev, Vladimir T. (Chemistry of Heterocyclic Compounds, 2020)
[Figure not available: see fulltext.] A new method for the preparation of isoxazolylvinyl ketones related to potential cytotoxic agents has been developed. In the first step, the reaction of furfuryl ketones with hydroxylamine hydrochloride affords the corresponding oximes. Further, the oxidative ring opening – ring closure reaction of oximes leads to isoxazoles with an α, β-unsaturated carbonyl motif. The developed procedure is metal-free and does not require expensive starting materials.
CRIS-Team Scopus Importer:2020-12-11
Keywords: chalcone; furan; isoxazole; ring opening – ring closure reaction

Synthesis of pyrazolylvinyl ketones from furan derivatives - Sawengngen, Nattawut; Chalikidi, Petrakis N.; Araby, Sara; Hampel, Frank; Gmeiner, Peter; Serdyuk, Olga (Organic & Biomolecular Chemistry, 2019)
A new protocol for the synthesis of pyrazol-5-ylvinyl ketones, e.g. pyrazole-chalcones, employing furfuryl ketones as a triketone equivalent, has been developed. The reaction occurs under mild conditions and does not require the use of expensive materials. Other important benefits include the simplicity and atom efficiency of this approach.
CRIS-Team Scopus Importer:2019-05-28